Assessment and litigation of ocular injuries by less-lethal weapons. - Pérez-Sales, Pau; Lopez Martin, Sara; Parras Cordoves, Marina (Torture Journal, 2024)
The main cause of serious ophthalmological injuries, including violent eye amputations in the context of so-called less lethal weapons, is the use of blunt objects, such as batons or extendable sticks and the use of kinetic energy projectiles (rubber bullets, pellets, foam projectiles or others). Such injuries in the context of population control have been considered to constitute cruel, inhuman or degrading treatment or even torture when they are carried out, intentionally or unintentionally, by State officials (or with their acquiescence or protection) and involve any of the purposes contemplated in the Convention against Torture. Due to their special characteristics, they constitute rights violations that entail unique difficulties and complexity from both a legal and forensic point of view. This paper addresses some of these difficulties with practical legal and forensic recommendations. It is structured in two parts: First, legal, where we consider legal difficulties and provide suggestions on elements for obtaining evidence are given. Second, medico-psychological and forensic where we review the elements to be considered in the interview, the medical and ophthalmological evaluation, and the psychometric, psychological and psychiatric evaluation.